2023
DOI: 10.1039/d2cc06948b
|View full text |Cite
|
Sign up to set email alerts
|

Zr- and Ti-based metal–organic frameworks: synthesis, structures and catalytic applications

Abstract: Recently, Zr- and Ti-based metal-organic frameworks (MOFs) have gathered increasing interest in the field of chemistry and material science, not only for their ordered porous structure, large surface area, high...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 176 publications
1
13
0
Order By: Relevance
“…This should be due to that steric hindrance makes the attack of Br – ions more difficult, consistent with previously reported studies. Furthermore, it is worth mentioning that the catalytic performance of NUC-101a in terms of reaction pressure, temperature, and time is better than or comparable to some activated metal–organic host frameworks such as TCM-16 (Zr), JLU-MOF58 (Zr), ZnMOF-1-NH 2 , MIL-101-H/pmtzm-Br, and CTP-1-NH 2 , shown in Table S7. The results indicate that the synergistic effect from Lewis acidic metal sites, nitrogen-rich groups, and high surface area plays a key role in improving the catalytic activity on the coupling reaction of CO 2 with epoxides. …”
Section: Resultsmentioning
confidence: 97%
“…This should be due to that steric hindrance makes the attack of Br – ions more difficult, consistent with previously reported studies. Furthermore, it is worth mentioning that the catalytic performance of NUC-101a in terms of reaction pressure, temperature, and time is better than or comparable to some activated metal–organic host frameworks such as TCM-16 (Zr), JLU-MOF58 (Zr), ZnMOF-1-NH 2 , MIL-101-H/pmtzm-Br, and CTP-1-NH 2 , shown in Table S7. The results indicate that the synergistic effect from Lewis acidic metal sites, nitrogen-rich groups, and high surface area plays a key role in improving the catalytic activity on the coupling reaction of CO 2 with epoxides. …”
Section: Resultsmentioning
confidence: 97%
“…22 In order to overcome the inert redox nature of Zr(IV) while benefiting from the exceptional chemical stability of Zr-based oxo-clusters, the development of heterometallic Ti/Zr-oxo clusters in MOFs has recently gathered increasing interest as recently reviewed. 23 Typically, Liu et al reported the introduction of Ti(IV) in UiO-66 via the formation of oxobridged hetero-Zr−Ti clusters allowing a photocatalyst efficient in the UV spectrum of light. 24 While the incorporation of Ti(IV) metal centers into the inorganic subnetwork of NH 2 −UiO-66 has been recurrently reported to enhance photocatalytic performances, 25−27 the possibility of forming supported TiO 2 nanoparticles rather than performing a Zr/Ti exchange when using PSM strategies has been also reported in UiO-66.…”
Section: ■ Introductionmentioning
confidence: 99%
“…More specifically, integrating different ligands and metals into the MOF structure can be achieved during the MOF synthesis ( in situ ); however, it can also be accomplished following a postsynthetic modification strategy (PSM) . In order to overcome the inert redox nature of Zr­(IV) while benefiting from the exceptional chemical stability of Zr-based oxo-clusters, the development of heterometallic Ti/Zr-oxo clusters in MOFs has recently gathered increasing interest as recently reviewed . Typically, Liu et al reported the introduction of Ti­(IV) in UiO-66 via the formation of oxo-bridged hetero-Zr–Ti clusters allowing a photocatalyst efficient in the UV spectrum of light .…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are porous hybrid materials consisting of organic linkers coordinated with metal ions or metal clusters. , MOFs possess desirable properties like good stability, large specific surface area, and controllable components. Hence, their popularizing applications include gas adsorption, chemical catalysis, bioimaging, and drug delivery. , Among them, UiO-66 has found wide application in drug delivery within the biomedical field. For example, Gupta et al designed UiO-66 for docetaxel drug delivery in vitro ; Chen et al reported the UiO-66 nanomaterial loading perfluorotributylamine/tirapazamine for osteosarcoma treatment .…”
Section: Introductionmentioning
confidence: 99%
“…24,25 MOFs possess desirable properties like good stability, large specific surface area, and controllable components. Hence, their popularizing applications include gas adsorption, 26 chemical catalysis, 27 bioimaging, 28 and drug delivery. 19,29 Among them, UiO-66 has found wide application in drug delivery within the biomedical field.…”
Section: Introductionmentioning
confidence: 99%